PERANCANGAN SISTEM AKSES KUNCI ELEKTRONIS PADA KOTAK PENYIMPANAN MEMANFAATKAN E-KTP DAN TEKNOLOGI RFID - Hani, Slamet; Santoso, Gatot; Hikam, Fahmi Bilbirril (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
Storage box has an important function which is often used to store valuables. In general, the locking system in a storage box is still conventional or manual, making it less practical. In addition, the level of security of the storage box must also be good. As a solution to both of the above, then it is necessary to design an electronic lock system in the storage box by using Electronic Identity Card (E-KTP) as the key access. In the E-KTP embedded chip that contains data that is different from one another. So, with these differences E-KTP can be used as a key. This electronic key system utilizes Radio Frequency Identification (RFID) technology, E-KTP as RFID tags, and Arduino Nano microcontroller. The UID (unique identity) data on the E-KTP will be read by the MFRC522 RFID reader. The data is then used as identification of certain E-KTPs that can be used to access electronic keys (in the form of DC solenoids) in the storage box. The results of the system control and output are in accordance with the plan. The E-KTP registered in the system can be used to access the storage box key. The voltage on the power supply and the Arduino Nano is in accordance with the requirements and in the test, the voltage error is not more than 10%, the MFRC522 RFID Reader is able to read the UID E-KTP data with reading distance 0 mm - 2 mm.